Fabrication of low elastic modulus Ti50Nb30HA20 alloy by rapid microwave sintering technique for biomedical applications. (2020) - Prakash, Chander; Singh, Sunpreet; Sharma, Shubham; Singh, Jujhar; Singh, Gursharan; Mehta, Munish; Mittal, Manoj; Kumar, Harish
Abstract: In the present study, low elastic modulus porous titanium (Ti50 ) niobium (Nb30 ) hydroxyapatite (HA20 ) alloy has been fabricated for orthopedic application by powder metallurgical and rapid microwave sintering process. The pores size in the synthesized alloy was 20–30 µm (μm). The HA element assists in the formation of structural porosity, which reduced the elastic modulus. The imposed structural porosity enhanced the bioactivity of the sintered alloy and reduced elastic modulus alleviates stress shielding effect. The fabricated alloy possessed low elastic modulus (12.67 GPa) and high porosity (21%).Moreover, various phases of biocompatibility such as tricalcium phosphate (Ca3 (PO4 )2 ) (generally referred as tri calcium phosphate (TCP)), Ti5P3 and calcium oxide (CaO) were formed during the sintering process benefited the tissue growth between the alloy-based implant and natural bone. Overall results highlighted the potential of the developed alloy for various possible orthopedic applications.